2004
DOI: 10.1158/0008-5472.can-03-4046
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Inhibits Multidrug Resistance Extrusion Pumps and Enhances Responses to Chemotherapy in Syngeneic and in Human Xenograft Mouse Tumor Models

Abstract: Multidrug resistance (MDR) operated by extrusion pumps such as P-glycoprotein and multidrug-resistance-associated-proteins, is a major reason for poor responses and failures in cancer chemotherapy. MDR modulators (chemosensitizers) were found among drugs approved for noncancer indications and their derivatives. Yet toxicity, adverse effects, and poor solubility at doses required for MDR reversal prevent their clinical application. Among newly designed chemosensitizers, some still suffer from toxicity and adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 27 publications
2
43
2
Order By: Relevance
“…Thus, fluoxetine may help a drug to be sensitive to tumor cells and accumulate to a sufficient level that culminates and undergoes cell growth inhibition (15,27). In addition to our observation in T24 cells, similar results of IFN-α in combination with fluoxetine were observed in human Jurkat-T, Huh7.5 and U2OS cells (data not shown).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, fluoxetine may help a drug to be sensitive to tumor cells and accumulate to a sufficient level that culminates and undergoes cell growth inhibition (15,27). In addition to our observation in T24 cells, similar results of IFN-α in combination with fluoxetine were observed in human Jurkat-T, Huh7.5 and U2OS cells (data not shown).…”
Section: Discussionsupporting
confidence: 83%
“…These studies have mainly been focused on the antiproliferative effects of FLX treatment in colon tumorigenesis [38,[63][64][65] . In cell culture models, FLX was reported to not only inhibit multidrug resistance and increase the intracellular doxorubicin concentration [66] , but also to induce a further nuclear distribution of this chemotherapeutic drug [67] .…”
Section: Flx Takes Energy Generation Un-der Control To Reduce Malignamentioning
confidence: 99%
“…FLX treatment seems to block tumor growth by breaking the malignant metabolism down [49,[52][53][54][55] . While the pieces for this puzzle are slowly being pulled together, there are already several reports which have given the ground ideas for following investigations [38][39][40]49,50,[52][53][54][55][56]58,60,61,[64][65][66][67][87][88][89][90][91][92]95] . Besides the specific idea of FLX acting against the tumor metabolism, there is an open question regarding the effects of FLX treatment against the "reverse Warburg effect".…”
Section: Perspectives In Flx Treatment Acting Against Colon Cancermentioning
confidence: 99%
“…On the other hand, several studies have reported that antidepressants increase the risk of nonHodgkin lymphoma and prostate cancer (5,6), and it is still controversial what effect tricyclic antidepressants have on lung, breast and colon cancer cells (7)(8)(9). Both in vitro and in vivo studies indicate antidepressants are cytotoxic to most malignant cells, particularly colon and breast cancer (10)(11)(12). The induction of apoptosis by DMI has been demonstrated to be significant in colon cancer, glioma and renal tubular cells (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%